Analisis Efektivitas Pelayanan Permohonan Perizinan Mendirikan Bangunan Dengan Berbasis Elektronik Serta Kontribusinya Pada Pendapatan Asli Daerah - Naswa Aziza Huwaida Rahmatunnisa; Sulistia Suwondo; Iyeh Supriatna (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The long bureaucracy in public services causes frequent fraud by irresponsible officials. As a form of improving public services, the government seeks to prevent this from happening by implementing One Stop Integrated Services and utilizing information technology with Electronic-Based Licensing Services. The electronic-based licensing service itself has been carried out by the City of Bandung under the auspices of DPMPTSP by using the HAY.U Bandung website-based service and the GAMPIL application since 2016. This research was conducted to analyze the effectiveness of the electronic-based licensing program and to what extent its contribution to PAD in Bandung City originates from levy for building permits. This study uses a qualitative method. The result of this research is the implementation of electronic-based licensing by implementation is considered quite effective but lacks in the aspect of program socialization. The contribution of IMB retribution in Bandung City PAD is still considered very insufficient, but it is reasonable because there is a tax sector which is the largest contribution.